ANALISIS ALOKASI BELANJA MODAL DALAM PENGENTASAN KEMISKINAN DI PEMERINTAH KABUPATEN SELUMA - Deviana, Deviana; Husaini, Husaini; Abdullah, Abdullah (JURNAL FAIRNESS, 2018)
This study aims to analyze the proportion of capital expenditures allocated and justified in poverty alleviation in the Seluma Regency. The sample of this research is five local government organizations (OPD) which are under the auspices of Seluma Regency. This study found that the allocation of capital expenditure for poverty alleviation during the period of 2014-2016 is fluctuated with the largest funds allocated in 2014 which amounted to 86,71% of total capital expenditure from Seluma Regency Budget and the smallest allocation of funds occurred in 2015 which amounted to 35,14% of total capital expenditure of Seluma Regency Budget. The study found that Seluma Regency has implemented poverty alleviation programs with high allocation of capital expenditure in activities related to poverty alleviation as the evidence.